A POSTMODERN PERSPECTIVE OF GEOGRAPHY AS AN INVESTIGATING SUPPORT OF EUROPE’S KNOWLEDGE-BASED ECONOMY - Mairie G. DOUDEXOPOULOU; Gabor BARTHA (European Journal of Geography, 2012)
The interdisciplinary character of geography involves a vast variety of knowledge under the two key meanings: “space” and “information”. The thematic maps are useful means to illustrate different sorts of qualified and raked “information”, with respect to a simplified representation of the geographical “space” and provide an easy and fast visualization of possibly existing relationships among different sorts of ranked data in cases that these cannot be obvious. The Education and Research (E&R) sectors belong to the economical resources and are also influential factors of an IT based economy. This double role motivated the authors to extend the postmodern perspective of g eography from only “space” to qualified“information”. Ranked information about R&D enterprise s and E&R resources of six European countries are shown in thematic maps to reveal the possible impact of E& R resources on R&D sector that characterize the so-called Society of Knowledge (SK).